2015
DOI: 10.1152/ajprenal.00449.2014
|View full text |Cite
|
Sign up to set email alerts
|

Urinary vimentin mRNA as a potential novel biomarker of renal fibrosis

Abstract: Renal fibrosis is a histological outcome of chronic kidney disease (CKD) progression. However, the noninvasive detection of renal fibrosis remains a challenge. Here we constructed a renal fibrosis target mRNA array and used it to detect urinary mRNAs of CKD patients for investigating potential noninvasive biomarkers of renal fibrosis. We collected urine samples from 39 biopsy-proven CKD patients and 11 healthy controls in the training set. Urinary mRNA profiles of 86 genes showed a total of 21 mRNAs that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
(18 reference statements)
1
25
0
Order By: Relevance
“…Recent findings have implied that TEC, MMP-9, and TIMP-2 expression can be upregulated by TGF-β in disease models2223. We previously reported that the expression of MMP9 mRNA was strongly correlated with kidney function parameters9. Here, we further showed that these two mRNAs could serve as TIF biomarkers.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Recent findings have implied that TEC, MMP-9, and TIMP-2 expression can be upregulated by TGF-β in disease models2223. We previously reported that the expression of MMP9 mRNA was strongly correlated with kidney function parameters9. Here, we further showed that these two mRNAs could serve as TIF biomarkers.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, these markers reveal limited information regarding the underlying molecular mechanism. Recent data have shown that measuring transcriptional differences in urine sediment from patients with CKD may provide a novel means for early and sensitive diagnosis789.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2a–e). Opn , a marker for vascular calcification23, Vim , a marker for kidney fibrosis24, and Ngal and Kim-1 , markers for tubular damage25, increased significantly in the CKD model mice compared with the control mice. αKlotho , another marker for kidney damage26, also decreased significantly in the CKD mice.…”
Section: Resultsmentioning
confidence: 97%
“…3 Renal fibrosis is the common pathological changes of CKD. 4 The development of epithelial-to-mesenchymal transition (EMT) of mature tubular epithelial cells leads to the accumulation and deposition of extracellular matrix (ECM), 5 which results in tissue fibrosis. Transforming growth factor beta1 (TGF-b1), a fibrosis-promoting cytokine, is involved in the process of EMT and ECM production.…”
Section: Introductionmentioning
confidence: 99%